Distribution of VA Mycorrhizal Spores in Sandy Beach Soils under Cashew - Hashim, Azizah Chulan; Yaacob, Othman; Kamal, A.J.M; Paramananthan, S (1983)
Surface horizons (0-15 em) of sandy beach soils from Besut and Kuantan, (Malaysia) under cashew (Anacardium occidentale L) were sampled for Vesicular-Arbuscular Mycorrhizal (VAM) spores. Isolation of VAM spores were made from both the Rudua and Jambu series in Besut as well as the Rudua and Baging series in Kuantan. There were more spores isolated from the Kuantan than the Besut areas. The results also indiate a positive relationship between spore number to percent organic matter present in the topsoil. The abundant spores isolated from the Kuantan areas (in contrast to Besut) could have some significance in the P nutrition of cashew and probably explain the yield differences existing between these two areas.